Pengaruh Marketing Mix Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Mujigae Resto Bekasi - Budi Satria; Dhian Tyas Untari; Fata Nidaul Khasanah (Jurnal Kajian Ilmiah, 2023)
This study aims to determine whether the marketing mix has an effect on consumer satisfaction at mujigae restaurants, whether service quality affects customer satisfaction at mujigae restaurants, and whether both have an effect on customer satisfaction at mujigae restaurants. The results obtained by the author in this study are for the marketing mix variable because the t count value is greater than t table (4.54 > 1.6648) and the significance value is less than 0.05 (0.000 < 0.05), it can be concluded that the marketing mix influences which is significant to customer satisfaction, for the service quality variable because the t value is greater than t table (5.99 > 1.6648) and the significance value is less than 0.05 (0.000 < 0.05), it can be concluded that service quality has a significant effect on customer satisfaction, and for the second effect because the calculated F value is greater than F table (73.193 > 3.11), and a significance value of 0.000 < 0.05, it can be concluded that the marketing mix and service quality have a positive and simultaneous effect on customer satisfaction.